Habitat fidelity in hawksbill sea turtles - Andrew S. Maurer; Julia A. Horrocks; Claudio Bellini; Karen L. Eckert; Alexandra L. Fireman; Mariana M. P. B. Fuentes; Barry Krueger; Kathryn E. Levasseur; Maria A. Marcovaldi; Renata M. A. Ramos; Seth P. Stapleton; Hannah B. Vander Zanden; et al. (Ecology, 2025)
Climate change is altering habitat suitability and driving shifts in species distributions. To understand potential responses by mobile animals, it is essential to assess levels of plasticity in habitat use, ranging from transience to long‐term fidelity. Here, we evaluate the fidelity of hawksbill sea turtles ( Eretmochelys imbricata ) to habitats used while foraging (our primary focus), migrating, and nesting. After satellite tracking 17 adult females from three Western Atlantic nesting areas, we then re‐tracked them in a subsequent year. Of 15 turtles with sufficient data to assess interannual foraging area fidelity, 14 returned to the same home range, exhibiting overlap between successive 50% utilization distributions (UDs); the 15th individual shifted

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Long-Term Follow-Up of Cerebral Aneurysms Completely Occluded at 6 Months After Intervention with the Woven EndoBridge (WEB) Device: a Retrospective Multicenter Observational Study - Kareem El Naamani; Panagiotis Mastorakos; Nimer Adeeb; Mathews Lan; James Castiglione; Omaditya Khanna; Jose Danilo Bengzon Diestro; Rachel M. McLellan; Mahmoud Dibas; Justin E. Vranic; Assala Aslan; Hugo H. Cuellar-Saenz; et al. (Translational Stroke Research, 2024)

Correction to: The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Characterizing azobenzene disperse dyes and related compounds in house dust and their correlations with other organic contaminant classes - Kirsten E. Overdahl; Christopher D. Kassotis; Kate Hoffman; Gordon J. Getzinger; Allison Phillips; Stephanie Hammel; Heather M. Stapleton; P. Lee Ferguson (Environmental Pollution, 2023)

The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis - Saeideh Esmaeili; Brett R. Jesmer; Shannon E. Albeke; Ellen O. Aikens; Kathryn A. Schoenecker; Sarah R. B. King; Briana Abrahms; Bayarbaatar Buuveibaatar; Jeffrey L. Beck; Randall B. Boone; Francesca Cagnacci; Simon Chamaillé‐Jammes; et al. (Ecology Letters, 2021)
The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and ruminants across biomes. Selection for intermediate forage biomass was negatively related to body size, regardless of digestive system. Selection for proximity to surface water was stronger for equids relative to ruminants, regardless of body size. To be more generalisable, we suggest that the FMH explicitly incorporate contingencies in body size and digestive system, with small‐bodied ruminants selecting more strongly for potential energy intake, and hindgut fermenters selecting more strongly for surface water.

Use of F-Specific RNA Bacteriophage to Estimate Infectious Norovirus Levels in Oysters - J. A. Lowther; L. Cross; T. Stapleton; N. E. Gustar; D. I. Walker; M. Sills; S. Treagus; V. Pollington; D. N. Lees (Food and Environmental Virology, 2019)

Creative Solution for Implementation of Experiential, Competency-Based Palliative Care Training for Internal Medicine Residents - Douglas D. Ross; Deborah W. Shpritz; Susan D. Wolfsthal; Ann B. Zimrin; Timothy J. Keay; Hong-Bin Fang; Carl A. Schuetz; Laura M. Stapleton; David E. Weissman (Journal of Cancer Education, 2011)

Polybrominated Diphenyl Ethers in American Eels (Anguilla rostrata) from the Delaware River, USA - J. T. F. Ashley; D. Libero; E. Halscheid; L. Zaoudeh; H. M. Stapleton (Bulletin of Environmental Contamination and Toxicology, 2007)

Effects of temperature variation on suicide in five U.S. counties, 1991–2001 - P. G. Dixon; A. N. McDonald; K. N. Scheitlin; J. E. Stapleton; J. S. Allen; W. M. Carter; M. R. Holley; D. D. Inman; J. B. Roberts (International Journal of Biometeorology, 2007)

Comparing Polybrominated Diphenyl Ether and Polychlorinated Biphenyl Bioaccumulation in a Food Web in Grand Traverse Bay, Lake Michigan - H. M. Stapleton; J. E. Baker (Archives of Environmental Contamination and Toxicology, 2003)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)